Occupational Noise Exposure and Age as Predictors of Disabling Hearing Loss in Pakistan - Huma Hanif; Ibtasam Thakur; Georgios P. Georgiou; Paris Binos (WISE Pendidikan Indonesia, 2026)
This study aimed to assess the prevalence, severity, and functional impact of hearing loss (HL) in Rawalpindi and Islamabad, Pakistan. A total of 400 participants, aged 12 to 70 years, were enrolled in the study, and data were collected using pure-tone audiometry (PTA) and the Hearing Handicap Inventory for Adults (HHIA). The results indicated that 18% of participants had some form of HL, with 22% meeting the criteria for disabling HL (≥35 dB HL). The severity of HL ranged from mild to profound, with 55% of participants exhibiting no measurable HL. Sensorineural HL was the most common type (60%), followed by conductive (24%) and mixed (10%) types. Bivariate analysis revealed that older age (≥60 years) and occupational noise exposure were significantly associated with HL ≥35 dB HL. The multivariable logistic regression model confirmed that age and occupational noise exposure were independent predictors of HL. Furthermore, hearing aid users reported significantly lower HHIA scores, indicating reduced psychosocial burden compared to non-users. This study highlights the need for early detection, public health interventions, and increased access to hearing aids, particularly in rural areas. The findings also demonstrate the importance of occupational noise control and workplace interventions to reduce the risk of HL in high-noise environments. The study contributes to the understanding of HL in Pakistan, offering valuable insights for improving hearing care accessibility and policy development.